Multi Partnership Model In Empowering Women Through Digitalization Of The Home Industry - Lidiati, Yanti; Hufad, Achmad; Ardiwinata, Jajat Sudrajat; Pramudia, Joni Rahmat; Putra, Apriza Hongko (Universitas Negeri Semarang, 2023)
Translator Translator Empowered women are agents of social change that starts with changes at the level of the individual, the family and then in the community where she lives and interacts. Similarly, in efforts to reduce poverty in rural areas, where a number of development actors jointly play a role in creating ecosystems that support the formation of women in the context of increasing women's economic productivity through the development of home industries.. The study uses a qualitative approach, with data collection techniques of interviews, observations and documentation, attended by five informants at the An-Nur Community Learning Center. Research results show that the digitization of the household industry is a breakthrough in ensuring that the activity and productivity of the home industry continues through digitization to facilitate product marketing access. This effort is a process of empowering women in the countryside, as the terminology of digitalization requires skills in using the Internet and other applications that are electronic or digital. The study concludes that the role of multi-stakeholder partnerships can accelerate the digitization of the home industry which opens up opportunities to acquire wider knowledge of skills for women with existing internet connections.